Individual Characteristics, Leadership, and Performance: The Dynamics of Lecturers In Papua and West Papua - Heatubun, Febianus; Echdar, Saban; Hasmin, Hasmin; Farsida, Umi (Green Publisher Indonesia, 2025)
This study aims to analyze the impact of individual characteristics, leadership, and performance of lecturers in Papua and West Papua, with Organizational Citizenship Behavior (OCB) and the Indonesian Higher Education Quality Assurance System (SPMI) acting as mediating variables. A quantitative approach was used for this research, with a sample size of 210 lecturers drawn from a population of 1,176 private university lecturers in these regions. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. The findings reveal that individual characteristics and leadership both have a positive and significant effect on OCB and SPMI. Furthermore, individual characteristics do not directly affect lecturer performance, whereas leadership has a significant positive impact on performance. OCB and SPMI were also found to positively influence lecturer performance. Additionally, individual characteristics and leadership were shown to affect lecturer performance indirectly through OCB and SPMI. These results provide insights into the factors that contribute to improving lecturer performance, emphasizing the critical roles of leadership and the mediating effects of OCB and SPMI.